Pink Glitter: Activist theatre against violence - Castillo, Debra A. (Latin American Theatre Review, 2022)
With the year of 2020 profoundly changed by COVID related travel and performance restrictions, we were forced to rethink how to continue to do theatre in the restricted context now available. As a consequence, during over two years of conversations in the ongoing pandemic, we had the luxury to rethink and rewrite the play Diamantina rosa/Pink Glitter without having a specific performance date as a limiting factor. This study documents the play’s development in several very different formats over a two year period:  the eventual scrapping of the original Spanish monologue/DJ set in favor of a more richly evolved in-person Spanish language live performance with multiple actors; the very different script and format for the two different online English language variations of the play; and the English language live performance.